(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The increase in the number of connected devices and the popularity of cloud computing has resulted in the generation of a large amount of data. These data need to be stored, transmitted, processed and analyzed. It can be applied to a variety of forward-thinking activities that foster wisdom and understanding. IoT and Cloud computing has become so popular that there is a need to integrate them. This integration is referred to as Cloud of Thing in this paper. This paper reviews the work in the sustainable practices of the cloud of things and gives direction for future research.